Treatment of posttraumatic stress disorder following childbirth - Lisa de Bruijn; Claire A. Stramrood; Mijke P. Lambregtse-van den Berg; Nathaly Rius Ottenheim (Journal of Psychosomatic Obstetrics and Gynecology, 2020)
Aim: The aim of this systematic review is to give an overview of the literature on treatment options for posttraumatic stress disorder (PTSD) following childbirth and to assess their efficacy. Method: PubMed, Embase, Web of Science, Cochrane and PsycINFO were searched using “PTSD”, “childbirth” and “therapy” as terms for studies in English language published between 2000 and 2017. Additional studies were identified by checking reference lists. Studies were included when presence of PTSD was confirmed prior to treatment and childbirth was the traumatic event focused on. All studies were reviewed on sample size, study design, used instruments, sample characteristics, type of treatment and the result of treatment regarding PTSD (symptoms). Results: Six studies met the inclusion criteria. One study on debriefing, three studies on cognitive behavioral therapy (CBT) and two studies on eye movement desensitization and reprocessing (EMDR) were identified. Both EMDR and CBT appear to be promising therapies for PTSD following childbirth. Debriefing seems to be beneficial when women request it themselves. Conclusions: EMDR and CBT seem to be effective as therapy for PTSD following childbirth. However, evidence is still limited and more controlled trials are needed to draw conclusive results.